2021
DOI: 10.1111/iej.13576
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial and immunomodulatory in vitro profile of double antibiotic paste

Abstract: Aim To evaluate the antimicrobial and immunomodulatory activity of double antibiotic paste (DAP) in an in vitro infection model. Methodology The minimum inhibitory and bactericidal concentrations (MIC and MBC) and the antibiofilm activities (TTC assay) of DAP and its components (ciprofloxacin and metronidazole) were evaluated against Staphylococcus aureus and Enterococcus faecalis compared with triple antibiotic paste (TAP). The cellular viability of RAW 264.7 macrophages (24 and 72 h) and L929 fibroblasts (48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Low concentrations of TAP and DAP reportedly have a similar capacity to reduce E. faecalis in vitro (Ferrer-Luque et al, 2021;Sabrah et al, 2015;Sousa et al, 2021). Whilst showing high clinical efficacy, TA has the disadvantage of inducing tooth discolouration due to minocycline (Ribeiro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of TAP and DAP reportedly have a similar capacity to reduce E. faecalis in vitro (Ferrer-Luque et al, 2021;Sabrah et al, 2015;Sousa et al, 2021). Whilst showing high clinical efficacy, TA has the disadvantage of inducing tooth discolouration due to minocycline (Ribeiro et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Among various peptides, IDR-1002 has demonstrated biotechnological potential for tissue engineering in endodontics [14]. A synergistic antimicrobial effect between the combination of IDR-1002 and cipro oxacin against E. faecalis and S. aureus was demonstrated [14]. This synergistic association presented interesting results not only in relation to the antimicrobial effect, but also interesting results relating to an immunomodulatory effect.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, several studies have explored the immunomodulatory pro le of these pastes. Until now, researchers have shown that TAP and DAP have pro-in ammatory activity [13,14]. It is known that the immune response plays an essential role in the regeneration of pulp tissue in IPT [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations